Lysozyme addition to slightly hypertonic nasal spray in the treatment of acute nasopharyngitis: a prospective post-marketing study - Pintol, Zumreta; Sukalo, Aziz; Mehic, Meliha; Tanovic Avdic, Amna; Baljic, Rusmir; Glamoclija, Una (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Acute nasopharyngitis is often treated with hypertonic saline that can be combined with additional compounds, such as lysozyme. The aim of this study was to compare efficacy and safety of hypertonic saline solution with or without lysozyme in the treatment of acute nasopharyngitis. Methods: Non-interventional, prospective, multicentre, observational, parallel study was conducted on adult subjects with symptoms of acute nasopharyngitis. Subjects were divided into hypertonic saline or lysozyme group (receiving slightly hypertonic nasal spray with addition of lysozyme). Time until the patency of both nasal passages was measured after the first application of therapy. The congestion severity was assessed by using a visual analogue scale before the therapy application, after 30 minutes, and after seven days. Adverse reactions were monitored and evaluated. Results: The total number of included subjects was 252 (60 in the hypertonic saline group and 192 in the lysozyme group). In both groups, a significantly better assessment of the severity of the nasal passages’ obstruction was recorded after 30 minutes and seven days from therapy start (for all compared time intervals p<0.001). The lysozyme group had a significantly lower nasal congestion score compared to hypertonic saline 30 minutes after therapy (p<0.001) and seven days from the therapy start (p=0.001). In the hypertonic saline group, a significantly shorter time was observed to establish the patency of the nasal passages after the first therapy application (p<0.001). All adverse events were mild. Conclusions: Addition of lysozyme to slightly hypertonic nasal spray brings added value in the pharmacotherapy of acute nasopharyngitis.